2022
DOI: 10.1021/acssuschemeng.2c01059
|View full text |Cite
|
Sign up to set email alerts
|

Depletion Effects and Stabilization of Pickering Emulsions Prepared from a Dual Nanocellulose System

Abstract: Nonadsorbing cellulose nanofibrils (CNF) are shown to induce stabilization of dilute oil-in-water Pickering emulsions formed by interfacial adsorption of highly charged TEMPO-oxidized CNF (TOCNF). The correlative interactions that occur upon sequential addition of the two types of nanofibrils (TOCNF and CNF) afford control of the properties of the obtained emulsions. For instance, the emulsions undergo (1) creaming of nonflocculated droplets at low CNF concentrations, (2) destabilization by depletion flocculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 43 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…In general, the mean droplet diameter (Figure 7b, except incomplete emulsions) showed a decreasing tendency with the increase of SNB concentration at day 1, and it became larger than that of day 1 after storage for 4 days, which was in agreement with previous studies. 28 Certainly, unstable emulsions presented the largest range of droplet diameter from 3.87 ± 1.07 to 9.87 ± 2.99 μm, and after storage for 4 days, even 13.57 ± 6.05 μm of diameter could be measured and apparent coalescence occurred (0.05 wt % SNB-stabilized emulsion), which further proved the instability of unstable emulsions. In terms of stable emulsions, from the images, it could be seen that the emulsion droplets with a mean diameter of around 2.5 μm were well separated and no apparent coalescence occurred, indicating that the appropriate SNB networks were formed in the oil-water interfaces and adequately stabilized the emulsions.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In general, the mean droplet diameter (Figure 7b, except incomplete emulsions) showed a decreasing tendency with the increase of SNB concentration at day 1, and it became larger than that of day 1 after storage for 4 days, which was in agreement with previous studies. 28 Certainly, unstable emulsions presented the largest range of droplet diameter from 3.87 ± 1.07 to 9.87 ± 2.99 μm, and after storage for 4 days, even 13.57 ± 6.05 μm of diameter could be measured and apparent coalescence occurred (0.05 wt % SNB-stabilized emulsion), which further proved the instability of unstable emulsions. In terms of stable emulsions, from the images, it could be seen that the emulsion droplets with a mean diameter of around 2.5 μm were well separated and no apparent coalescence occurred, indicating that the appropriate SNB networks were formed in the oil-water interfaces and adequately stabilized the emulsions.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…In general, the mean droplet diameter (Figure b, except incomplete emulsions) showed a decreasing tendency with the increase of SNB concentration at day 1, and it became larger than that of day 1 after storage for 4 days, which was in agreement with previous studies . Certainly, unstable emulsions presented the largest range of droplet diameter from 3.87 ± 1.07 to 9.87 ± 2.99 μm, and after storage for 4 days, even 13.57 ± 6.05 μm of diameter could be measured and apparent coalescence occurred (0.05 wt % SNB-stabilized emulsion), which further proved the instability of unstable emulsions.…”
Section: Resultsmentioning
confidence: 99%
“…52 Most applications of nanocellulose as Pickering stabilizer involve alkanes, vegetable oils, and several sorts of long-chain aliphatic compounds as the organic phase. 27,31,43 However, in our case, chloroform has a dipole moment of 1.15 D and it is a fair hydrogen bond donor. 53 Although the aforementioned simulation of a chloroform-solvated oxidized cellobiose molecule returned a positive value for free energy, dipole− dipole interactions were the highest contributors to energy minimization.…”
Section: Mechanism and Limitationsmentioning
confidence: 61%
“…Our proposal involves nanocellulose to stabilize a resembling system, although with less CHCl 3 and much less acid. Negatively charged cellulose nanofibers (CNFs) can simultaneously fulfill the roles of rheology modifier and Pickering stabilizer, which are generally closely related. , …”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanofibers (CNFs) are promising emulsifiers for Pickering emulsions offering amphiphilic character, biocompatibility, and sustainability. Several works demonstrated that surface-carboxylated CNFs by 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) exhibited higher stability than unmodified CNFs owing to the negative surface charge. Fujisawa et al reported that the cellulose origin should not significantly impact the formation of Pickering emulsions. Inspired by their research, we previously studied TEMPO-oxidized CNFs isolated from agricultural waste hop stems (HS) as an emulsifier for oil-in-water Pickering emulsions using dodecane or olive oil as the oil .…”
Section: Introductionmentioning
confidence: 99%